The genome of Desulfotalea psychrophila , a sulfate‐reducing bacterium from permanently cold Arctic sediments - R. Rabus; A. Ruepp; T. Frickey; T. Rattei; B. Fartmann; M. Stark; M. Bauer; A. Zibat; T. Lombardot; I. Becker; J. Amann; K. Gellner; et al. (Environmental Microbiology, 2004)
Summary Desulfotalea psychrophila is a marine sulfate‐reducing δ‐proteobacterium that is able to grow at in situ temperatures below 0°C. As abundant members of the microbial community in permanently cold marine sediments, D. psychrophila ‐like bacteria contribute to the global cycles of carbon and sulfur. Here, we describe the genome sequence of D. psychrophila strain LSv54, which consists of a 3 523 383 bp circular chromosome with 3118 predicted genes and two plasmids of 121 586 bp and 14 663 bp. Analysis of the genome gave insight into the metabolic properties of the organism, e.g. the presence of TRAP‐T systems as a major route for the uptake of C 4 ‐dicarboxylates, the unexpected presence of genes from the TCA cycle, a TAT secretion system, the lack of a β‐oxidation complex and typical Desulfovibrio cytochromes, such as c 553 , c 3 and ncc. D. psychrophila encodes more than 30 two‐component regulatory systems, including a new Ntr subcluster of hybrid kinases, nine putative cold shock proteins and nine potentially cold shock‐inducible proteins. A comparison of D. psychrophila 's genome features with those of the only other published genome from a sulfate reducer, the hyperthermophilic archaeon Archaeoglobus fulgidus , revealed many striking differences, but only a few shared features.

Initial reactions of anaerobic metabolism of alkylbenzenes in denitrifying and sulfate-reducing bacteria - R. Rabus; J. Heider (Archives of Microbiology, 1998)